Collaborative insights on horizontal logistics to integrate supply chain planning and transportation logistics planning – A systematic review and thematic mapping - Ahmed Zainul Abideen; Shahryar Sorooshian; Veera Pandiyan Kaliani Sundram; Ahmed Mohammed (Journal of Open Innovation: Technology, Market and Complexity, 2023)
The growth of digital platforms and information sharing in the supply chain and logistics arena has considerably improved cross-departmental and inter-organizational collaboration. A competitor backs another competitor to support their transportation and logistics activities for mutual benefit and growth over several echelons. On that note, there is a need for a solid horizontal collaboration framework within the supply chain network to ease the collaboration between transportation logistics and supply chain planning. This study has integrated a systematic review of past literature and a bibliometric analysis of the acquired data set. Most relevant keywords were used in the keyword search covering all the major databases. From the final data set, various insights on how collaborative supply chain and transportation network design, profit‐sharing, inventory bundling, and distribution, vehicle routing, and transport planning should be designed to attain optimal horizontal collaboration. The findings also portray the future research prospects on horizontal collaboration, practical research gaps, and related enablers within supply chain planning with a conceptual framework.